BUILDING COMMUNICATION SKILLS THROUGH FLIPPED CLASSROOM - Farina Nozakiah Tazijan; Sakina Sofia Baharom; Azianura Hani Shaari (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Flipped or inverted classroom has become a trend and a popular method of teaching and learning in educational practice. However, not many studies have been done in the practice of teaching English as a Second Language (ESL) in Malaysia. This paper discusses the use of flipped learning as a method to teach communication skills among a group of ESL learners in one higher learning institution. The study generally aims to analyse the effectiveness of flipped classroom method in enhancing students’ communication skills and abilities. The sample of respondents comprised of 75 ESL learners who were selected to undergo a five-week flipped communicative language program, which was designed to promote active learning and greater classroom engagement among its learners. Findings indicate a positive relationship between flipped teaching and active learning, thus improved learners’ verbal communication skills in certain ways.